2007
DOI: 10.4049/jimmunol.178.12.8148
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Stromal-Derived Factor-1 Expression and Effect on Neutrophil Recruitment during Acute Lung Injury

Abstract: The severe and protracted inflammation that characterizes acute lung injury (ALI) is driven by the ongoing recruitment of neutrophils to the lung. Although much of the cytokine signaling responsible for the initial phase of ALI has been elaborated, relatively little is known about the mechanisms governing the recruitment of neutrophils from the bone marrow to the lung in the later period of this disease. Given its previously described chemoattractant effects on marrow neutrophils, we investigated whether strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 70 publications
8
98
0
Order By: Relevance
“…Previous reports by our group and other investigators have shown that CXCL12 levels are upregulated in injured lungs and that in vivo administration of anti-CXCL12 blocking antibodies suppresses airspace neutrophilia in the lungs at the later stages of LPS-induced lung injury, [17][18][19] suggesting that the increase of surface CXCR4 expression on lung extravasated neutrophils cooperates with the increase of CXCL12 in the lungs to facilitate the accumulation of neutrophils. To confirm the in vivo role of the CXCL12/CXCR4 signaling system in the pathogenesis of acute lung injury, we administrated a specific CXCR4 antagonist to block the activation of CXCR4.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous reports by our group and other investigators have shown that CXCL12 levels are upregulated in injured lungs and that in vivo administration of anti-CXCL12 blocking antibodies suppresses airspace neutrophilia in the lungs at the later stages of LPS-induced lung injury, [17][18][19] suggesting that the increase of surface CXCR4 expression on lung extravasated neutrophils cooperates with the increase of CXCL12 in the lungs to facilitate the accumulation of neutrophils. To confirm the in vivo role of the CXCL12/CXCR4 signaling system in the pathogenesis of acute lung injury, we administrated a specific CXCR4 antagonist to block the activation of CXCR4.…”
Section: Resultsmentioning
confidence: 95%
“…Because CXCL12 is also upregulated in the injured lungs, [17][18][19] these findings suggest that the increase in surface CXCR4 expression levels on extravasated neutrophils acts together with the increase of CXCL12 in the lungs to promote neutrophil migration and/or retention within the airspace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petty et al identified stromal cell-derived factor (SDF)-1 as the major chemokine important in sustained neutrophilic responses in the endotoxin-treated murine lung [70]. They also demonstrated the progressive upregulation of its receptor CXCR4 on neutrophils.…”
Section: Release Of Chemokines Cytokines and Other Inflammatory Modulamentioning
confidence: 99%
“…CXCL12/CXCR4 not only regulates the development of T and B lymphocytes but also contributes to the survival of mature lymphocytes and in the generation of memory T cells (Klein RS and Rubin JB, 2004). Recent studies indicate that CXCL12/CXCR4 enhances the inflammatory infiltration of neutrophils or lymphocytes in diverse models and settings involving acute inflammation or fulminant infection (Wald O et al, 2004;Ding Z et al, 2006;Petty JM et al, 2007). CXCL12 is an important regulator for homing of hematopoietic progenitor cells (HPCs) to the bone marrow (BM) microenvironment (Lapidot T et al, 2005).…”
Section: Introductionmentioning
confidence: 99%